Factors Influencing Customs Delays at Kribi Port: A Case Study of Containerized Goods - (:unkn) unknown (My University, 2025)
This research investigates the customs clearance procedure for containerized cargo at the Port of Kribi, Cameroon, using a quantitative explanatory approach to determine delay factors, evaluate their socio-economic consequences, and recommend policy-sensitive changes. Data collection was achieved through 359 valid responses from a stratified random sample of participants which included customs brokers, shipping lines, customs officers, import-export agents, SGS Cameroon, and port administrators which formed an 87% response rate. Descriptive results identified major delay factors which include insufficient financial resources, limited scanning equipment, red tape, poor interagency collaboration, and lack of agency cooperation. A chi-square test of independence showed a significant relationship between stakeholder group and perceived cause of delay (χ² = 84.76, df = 24, p < .001) thus confirming the research hypothesis while Cramér’s V 0.243 indicated small to moderate effect size suggesting differing perceptions across stakeholder groups. Such inefficiencies lead to increased delays in clearance time, increased demurrage costs, higher operational expenses, reduced customer satisfaction, and a decrease in the port’s competitiveness. For these issues, the study proposes full digitization of the customs and port system, enhancement of training for identified key players, and aligning customs policies to international benchmarks of trade facilitation as areas of design interventions.
Keywords: African Research